A hybrid symbolic-numerical approach to the center-focus problem. (September 2017) - Mahdi, Adam; Pessoa, Claudio; Hauenstein, Jonathan D.
Abstract: We propose a new hybrid symbolic-numerical approach to the center-focus problem. The method allowed us to obtain center conditions for a three-dimensional system of differential equations, which was previously not possible using traditional, purely symbolic computational techniques.